The impact of morphological changes in the urban fabric on the identity of heritage areas, the case of Bou-Saada Palace - Dogha, Mohamed Sofiane; Faid, Bachir (Journal of Architecture and environment of child, 2024)
With the modern urban, social and economic developments in cities, many heritage areas are under threat of the disappearance of their authentic urban identity, These areas, including Bou-Saada Palace, which is rich in authentic urban heritage, began to suffer in its urban fabric from the predominance of its modern character, due to the loss of the heritage elements it contains on the one hand, and the incompatibility of modern urban development (planned and random urban interventions) in most cases with its original urban identity from the other side, Through our research, we aim to diagnose the reality of morphological changes in the elements of the urban fabric of Bou Saada Palace, and try to address this in order to preserve and protect it, relying in this on the “descriptive and analytical approach” and its diagnosis of the heritage area of Bou-Saada Palace, In addition to the inductive approach to determine the morphological changes that occurred on its urban fabric and the extent of their impact on its urban identity first, then providing solutions and suggestions that would achieve the preservation of the urban identity of Bou Saada Palace and its rehabilitation.